Antenatal depression and associated factors among pregnant women attending antenatal care at public health facilities in the Gida Ayana district, Oromia Region, West Ethiopia, in 2022 - Lelisa Oljira; Eba Abdissa; Matiyos Lema; Emiru Merdassa; Jira Wakoya Feyisa; Markos Desalegn (Frontiers Media S.A., 2023)
BackgroundThough antenatal depression (AND) has a risk of maternal and fetal morbidity and mortality, it is a neglected component of pregnancy care in Ethiopia. Research evidence is compulsory in different parts of the country to alleviate this problem. Thus, this study was needed to assess antenatal depression and its associated factors, which can help antenatal care (ANC) providers and program coordinators focus on the mental health of pregnant mothers.ObjectivesThis study aimed to assess antenatal depression and associated factors among pregnant women attending ANC at public health facilities in the Gida Ayana district, Oromia Region, West Ethiopia, in 2022.MethodsA facility-based cross-sectional study was conducted among 370 pregnant women attending ANC at public health facilities. Systematic random sampling techniques were used to select study participants. A standard (validated) tool, the Edinburgh Postnatal Depression Scale, was also used to assess antenatal depression. The collected data were coded, entered into Epi-data software version 4.6, and analyzed by SPSS version 23. Multivariable logistic regression analyses were used to identify associated factors with a p-value <0.05.ResultsIn this study, the prevalence of antenatal depression was 62 (16.8%; 95% CI: 13, 20.5). Being single in marital status (AOR = 3, 95% CI: 1.5, 6.2), having an unplanned pregnancy (AOR = 2.7, 95% CI: 1.45, 5.1), and having partner conflict (AOR = 3.49, 95% CI: 1.79, 6.8) were the factors associated with antenatal depression.ConclusionAbout one in five pregnant women has antenatal depression. Being single, having an unplanned pregnancy, and having a dissatisfied relationship with a sexual partner were the factors associated with antenatal depression. Therefore, women or partners are expected to plan pregnancy, and the dissemination of health information related to an unplanned pregnancy needs to be intensified by health providers. The partner ought to avoid conflict during the pregnancy, and healthcare providers or families are needed to support the single or widowed pregnant women. Further prospective cohort studies are needed to ascertain the effect of antenatal depression on fetal-maternal outcomes.